Propafenone HCl fast dissolving tablets containing subliming agent prepared by direct compression method - Saleh Abd El Rasoul; Gamal A. Shazly (Elsevier, 2017)
Propafenone HCl (PPH), an antiarrhythmic drug, has a bitter taste, short half-life, delayed drug dissolution and side effects. Thus, the purpose of this work is to develop orally fast dissolving tablets (OFDTs) containing PPH to provide a rapid drug dissolution and subsequently give rapid onset of action of PPH as an antiarrhythmic drug. Moreover, OFDTs of PPH reduce its side effects and improve its bioavailability. Propafenone HCl (PPH), an antiarrhythmic drug, has a bitter taste, short half-life, delayed drug dissolution and side effects. Direct compression method was used for the preparation of 15 formulations OFDTs containing PPH using directly compressible excipients, subliming agent and superdisintegrants. The prepared tablets were undergone physical characterization, in vitro dissolution and stability studies. All pre- and post-compression tests met the pharmacopoeia specifications. In vitro dissolution of the prepared PPH OFDTs exhibited high dissolution rate than compared to the marketed tablets. It was found that the tablets prepared by using the higher concentration of crospovidone were found to dissolute the drug at a faster rate when compared to other concentrations. A formula containing croscarmellose sodium showed the higher present of PPH dissolved as compared to the other formulations. It was concluded that PPH OFDTs were formulated successfully with acceptable physical and chemical properties with rapid disintegration in the oral cavity, rapid onset of action, and enhanced patient compliance. It was found that F10 showed good stability upon storage at 25 and 40 °C for 3 months. Formulation of PPH OFDTs can result in a significant improvement in the PPH bioavailability since the first pass metabolism will be avoided.